Multimorbidity in Antineutrophil Cytoplasmic Antibody–Associated Vasculitis: Results From a Longitudinal, Multicenter Data Linkage Study. Issue 4 (5th March 2021) - Sarica, Shifa H.; Gallacher, Peter J.; Dhaun, Neeraj; Sznajd, Jan; Harvie, John; McLaren, John; McGeoch, Lucy; Kumar, Vinod; Amft, Nicole; Erwig, Lars; Marks, Angharad; Bruno, Laura; et al.
Abstract : Objective: Antineutrophil cytoplasmic antibody–associated vasculitis (AAV) is considered a chronic, relapsing condition. To date, no studies have investigated multimorbidity in AAV nationally. This study was undertaken to characterize temporal trends in multimorbidity and report excess health care expenditures associated with multimorbidities in a national AAV cohort from Scotland. Methods: Eligible patients with AAV were diagnosed between 1997 and 2017. Each patient was matched with up to 5 general population controls. Linked morbidity and health care expenditure data were retrieved from a Scottish national hospitalization repository and from published national cost data. Multimorbidity was defined as the development of ≥2 disorders. Prespecified morbidities, individually and together, were analyzed for risks and associations over time using modified Poisson regression, discrete interval analysis, and chi‐square test for trend. The relationship between multimorbidities and health care expenditure was investigated using multivariate linear regression. Results: In total, 543 patients with AAV (median age 58.7 years [range 48.9–68.0 years]; 53.6% male) and 2, 672 general population controls (median age 58.7 years [range 48.9–68.0 years]; 53.7% male) were matched and followed up for a median of 5.1 years. AAV patients were more likely to develop individual morbidities at all time points, but especially <2 years after diagnosis. The highest proportional risk observed was for osteoporosis (adjusted incidence rate ratio 8.0, 95% confidence interval [95% CI] 4.5–14.2). After 1 year, 23.0% of AAV patients and 9.3% of controls had developed multimorbidity ( P < 0.0001). After 10 years, 37.0% of AAV patients and 17.3% of controls were reported to have multimorbidity ( P < 0.0001). Multimorbidity was associated with disproportionate increases in health care expenditures in AAV patients. Health care expenditure was highest for AAV patients with ≥3 morbidities (3.89‐fold increase in costs, 95% CI 2.83–5.31; P < 0.001 versus no morbidities). Conclusion: These findings emphasize the importance of holistic care in patients with AAV, and may identify a potentially critical opportunity to consider early screening.